2020
DOI: 10.7717/peerj.8829
|View full text |Cite
|
Sign up to set email alerts
|

ARF family identification in Tamarix chinensis reveals the salt responsive expression of TcARF6 targeted by miR167

Abstract: Auxin response factors (ARFs) are important transcription factors (TFs) that are differentially expressed in response to various abiotic stresses. The important roles of ARFs and small RNA-ARF pathways in mediating plant growth and stress responses have emerged in several recent studies. However, no studies on the involvement of ARFs in tamarisk trees, which are resistant to salinity, have been conducted. In this study, systematic analysis revealed 12 TcARF genes belonging to five different groups in Tamarix c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 52 publications
2
21
0
Order By: Relevance
“…miR167 as well as miR159 regulate the hormone signaling pathway of their targets, which are transcription factors. miR167 targets auxin response factor 8 (ARF8) in wheat and indole-3-acetic acid-alanine resistant3 (IAA-IAR3) in A. thaliana [43][44][45][46]. ARF genes are involved in the regulation of auxin response genes [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miR167 as well as miR159 regulate the hormone signaling pathway of their targets, which are transcription factors. miR167 targets auxin response factor 8 (ARF8) in wheat and indole-3-acetic acid-alanine resistant3 (IAA-IAR3) in A. thaliana [43][44][45][46]. ARF genes are involved in the regulation of auxin response genes [45].…”
Section: Discussionmentioning
confidence: 99%
“…miR167 targets auxin response factor 8 (ARF8) in wheat and indole-3-acetic acid-alanine resistant3 (IAA-IAR3) in A. thaliana [43][44][45][46]. ARF genes are involved in the regulation of auxin response genes [45]. It has been demonstrated that some plant pathogens produce auxin-like compounds or change the auxin signaling in plants and consequently increase the host's susceptibility to infection [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…The research progress of miR167 in recent years is detailed in Table 1 (Ref. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]).…”
Section: Csarf8mentioning
confidence: 99%
“…4.4.2 miR167 regulates abiotic stresses in plants miR167 plays a role in abiotic stress and is induced under high salinity and drought stress [95]. UV-B radiation caused an up-regulation of miR167 expression in Populus tremula [96], and miR167 targeted TcARF6 in Tamarix chinensis under salt stress [19]. The expression of miR167 under salt stress was analyzed by microarray hybridization, which was caused by different salt sensitivity of different species, it was found that the expression of miR167 in salttolerant cotton was up-regulated compared with that in saltsensitive cotton [97].…”
Section: Mir167mentioning
confidence: 99%
“…Many salt-responsive miRNAs were already discovered in plants, such as miR156 [29], miR159 [30], miR164 [31], miR167 [32,33], miR171 [34], miR319 [35], miR395 [36] and so forth. In S. pennelli, sly-miR156d-5p, sly-miR156e-5p, sly-miR395a, sly-miR395b, sly-miR5302a and sly-miR6022 could target 2 lncRNAs.…”
Section: The Function Of Lncrnas Acting As Mirna Targets In Tomatoesmentioning
confidence: 99%